Pavement life variation with material characteristics, road profiles and environmental effects - Buhari, Rosnawati; Md Rohani, Munzilah; Puteh, Saifullizam (Indonesian Society for Knowledge and Human Development, 2018)
Long-term performance of pavements is dependence on several aspects include design and method of construction, vehicles loading and environmental conditions along their service life. The pavement response to these aspects is mostly based on the stiffness characteristic of the materials. The most significant stiffness property is the resilient modulus that is based on the strain under loads and several factors include roughness of road profile, soil property, soil type and stress state. This study focus on the simulation of the pavement performance by considering pavement material and vehicle characteristic, road roughness and temperature variations. The vehicle-road interaction is the main focus. It includes analysis of the integration of damage consequence by the static and dynamic loads of the vehicle fleet on the structural variability of the pavement. Meanwhile, other factors such as, temperature influencing the modulus degradation of the bituminous material is also included. As a result all factors were significantly contributed to the life of the pavement.